2019
DOI: 10.1039/c8ra09632e
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and thermal decomposition mechanism of nitrocellulose/Cr2O3 nanoparticles studied using DSC and TG-FTIR

Abstract: Cr2O3 have good compatibility with nitrocellulose and catalyze decomposition of NC through decrease the activation energy. The mechanism showed Cr2O3 can accelerate the O–NO2 bond cleavage and speed up the secondary reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…F I G U R E 4 Thermogravimetric analysis (TGA)-DTG curves of the reference material divided in three steps: (1) First mass loss step; (2) second mass loss step; (3) organic decomposition.The samples R-g and Rm show a single-step (3), whereas R-s also shows steps (1) and (2) (with 4.3% ± 0.1% and 9.5% ± 1.9% mass loss respectively) before step 3It has been documented in the literature that the organic decomposition of pure CN results in the evolution of H 2 O, CO 2 , CO, HCOOH, N 2 O, NO, NO 2 and HCHO. [28][29][30] This study confirms such results with the addition of camphor and the exception of NO 2 and HCHO. Camphor is present due to the fact that the samples are made of celluloid.…”
Section: Gel Permeation Chromatographysupporting
confidence: 83%
See 1 more Smart Citation
“…F I G U R E 4 Thermogravimetric analysis (TGA)-DTG curves of the reference material divided in three steps: (1) First mass loss step; (2) second mass loss step; (3) organic decomposition.The samples R-g and Rm show a single-step (3), whereas R-s also shows steps (1) and (2) (with 4.3% ± 0.1% and 9.5% ± 1.9% mass loss respectively) before step 3It has been documented in the literature that the organic decomposition of pure CN results in the evolution of H 2 O, CO 2 , CO, HCOOH, N 2 O, NO, NO 2 and HCHO. [28][29][30] This study confirms such results with the addition of camphor and the exception of NO 2 and HCHO. Camphor is present due to the fact that the samples are made of celluloid.…”
Section: Gel Permeation Chromatographysupporting
confidence: 83%
“…14,[25][26][27] However, when employed with the simultaneous identification of the evolved gases of nitrocellulose, which the hyphenated technique TGA-FTIR can provide, studies focused on highly-nitrated (nitrogen >12%) energetic material (that is dynamites and gun propellants). [28][29][30] Given that museum collections mostly comprise low-nitrated (nitrogen <12%) objects plasticized with camphor, which have been rarely examined, this study employs TGA-FTIR to understand their thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4d, the bare ss304 exhibits a new broad peak at 662 cm −1 due to the formation of (Fe,Cr) 2 O 3 products on the steel surfaces after high-temperature annealing. 37,38 Importantly, for the case of the h-BNnanofilm-coated ss304, no additional peaks appear after annealing, evidencing its antioxidation protective ability for ss304. As a matter of fact, the h-BN nanofilms grown with different thicknesses and morphologies were also tested for the oxidation resistance properties at high temperatures.…”
Section: Resultsmentioning
confidence: 93%
“…It can be confirmed that Cu‐en significantly promotes the thermal decomposition of NC. The thermal decomposition of NC starts with the breaking of the O‐NO 2 bond to form NO 2 gas [28]. According to the characteristics of Cu described earlier, Cu will inevitably accelerate the breaking process of O‐NO 2 bond.…”
Section: Resultsmentioning
confidence: 99%